Spinning Q-balls in Five-Dimensional Spacetime - Bintoro anang subagyo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
We investigate q-balls in the d=5 dimensional Minkowski spacetime background with axially symmetricansatz. In this case, q-balls have non-zero angular momentum for spinning problems. We construct spinningq-balls in five dimensions and solve the solutions of second order elliptic partial differential equations bothusing analytical and numerical approach since no closed form of the equations following by appropriateboundary conditions. This work only considers the case with equal angular momentum rather than twodifferent angular momenta. Passing the solutions, we discuss the global charge and their properties comparedto Coleman q-balls. The solutions exist in some range of frequencies. The main features of q-balls are stillrecovered in this construction.